2008
DOI: 10.1016/j.jcs.2007.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Milling characteristics and distribution of phytic acid and zinc in long-, medium- and short-grain rice

Abstract: Milling and polishing are important operations during the production of white rice. The degree of milling and polishing has a significant effect on the nutritional aspects of white rice, especially on minerals, due to a non-uniform distribution of nutrients in the kernel. Information on the distribution of nutrients in rice will greatly help to understand the effect of milling and aid in designing procedures that improve technological and sensory properties of rice while retaining its essential nutrients as mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
75
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 24 publications
11
75
0
2
Order By: Relevance
“…10%) zinc content was reduced by half. While some previous studies had observed a negligible (Doesthale et al, 1979) or relatively modest decline (Liang et al, 2008) in zinc content of rice with 10-12% degree of milling, the magnitude of decrease observed in this study of 10 Bangladeshi rice varieties is consistent with the range observed in other studies. A 10-12% degree of milling resulted in retention of zinc of 73% (Villareal et al, 1991) and 55% (Pedersen and Eggum, 1983) compared to brown rice.…”
Section: Zinc and Phytate Contents Of Brown And Milled Rice By Degreesupporting
confidence: 92%
“…10%) zinc content was reduced by half. While some previous studies had observed a negligible (Doesthale et al, 1979) or relatively modest decline (Liang et al, 2008) in zinc content of rice with 10-12% degree of milling, the magnitude of decrease observed in this study of 10 Bangladeshi rice varieties is consistent with the range observed in other studies. A 10-12% degree of milling resulted in retention of zinc of 73% (Villareal et al, 1991) and 55% (Pedersen and Eggum, 1983) compared to brown rice.…”
Section: Zinc and Phytate Contents Of Brown And Milled Rice By Degreesupporting
confidence: 92%
“…Thus, milling and processing generally reduce the concentration of Zn in the edible product (Bityutskii et al 2002;Ozturk et al 2006;Liang et al 2008;Cakmak et al 2010;Joy et al 2015). Many of the studies included in the metaanalysis only reported Zn concentrations in whole grain, with and without application of Zn.…”
Section: Baseline Dietary Zn Supplies and Deficiency Prevalencementioning
confidence: 99%
“…Self-absorption of primary X-rays and emitted X-ray fluorescence may be caused by the relative thickness of a fixed droplet (from several tens to several hundreds of ÎŒm). However, Liang et al (2008) successfully visualized X-ray fluorescence images of K, Ca and Fe at different depths (200, 400, and 500 ÎŒm) in a kernel of rice grain. The samples in the present study were quite thin (50 ÎŒm) compared to a rice grain, and homogenous elemental distribution were less affected by the selfabsorption of X-rays.…”
Section: Visualization and Relative Quantification Of Elements In Amentioning
confidence: 99%